Productivity of semi-dry rice under simultaneous IN SITU green manuring - Musthafa Kunnathadi (Department of Agronomy, College of Horticulture, 1995)
An investigation aimed to study the influence of simultaneous in situ green manuring on the growth, yield and nutritional characteristics of rice was conducted during the first crop season of 1993 – 94 in the sandy clay loam soils of the Agricultural Research Station, Mannuthy. The treatments consisted of factorial combinations of four levels of nitrogen (0,35,70 and 105 kg N ha-1), two levels of phosphorus ( 0 and 35 kg P2O5 ha-1) and two seed rates of cowpea (15 and 30 kg ha-1) for in situ green manuring and a control without green manure. Cowpea was raised in alternate rows of rice. The experiment was laid out in RBD with three replications. Results of the study showed that simultaneous in situ raising of cowpea for green manure can be successfully practiced in semi-dry rice for improving the productivity. At the recommended level of fertilizers (70:35:35 kg N, P2O5, K2 O ha-1) a lower seed rate of cowpea was found to be the best which gave 24 and 64 per cent more yield of grain and straw, respectively than the recommended practice. However, a higher seed rate of cowpea was required if the level of N was limited to 35 kg ha-1. The system added 58 and 76 q of green matter ha-1 at the lower and higher seed rates, respectively. The system effectively minimised the production and decline of non productive tillers in the post flowering phase and contributed to the increased yield. The increased efficiency of plant N achieved in the system appeared to arise from a widening of N/Fe ratio as well as a regulatory influence on elements in the plant system. Intercropping of cowpea for green manure increased the incidence of leaf roller and sheath blight marginally. The system also suppressed the weed growth in the cropped field and the weed biomass production declined by 45 per cent by 20 DAS. Weeds removed larger quantities of K and Mg than rice and deplete the soil of these nutrients. Intercropping effectively checked this. The suppression effect was not uniform on all types of weeds. Sedges showed a tendency to increase when broad leaved weeds declined. Grassy weeds remained unaffected. Thus simultaneous in situ green manuring appears to change the weed spectrum in rice fields. A comparative analysis of the weather pattern during the season with that of the normal showed that the system can be successfully adopted in similar areas.